Island bioarchaeology and ritual knowledge transfer at Biniadrís cave (Menorca, Spain): a longue durée perspective - Díaz Zorita Bonilla, Marta; Timm, Monice; Marciales Daza, Mauricio; Moreno Onorato, Auxiliadora; Alarcón García, Eva; Karakostis, Alexandros F.; Escudero Carrillo, Javier; Arboledas Martínez, Luis; Robles Carrasco, Sonia; Morell, Berta; Hamilton, Derek; Dawson, Helen; et al. (Frontiers in Environmental Archaeology, 2025)
The Biniadrís cave is located in the southern part of the island of Menorca (Spain). It is the fourth funerary cave with preserved materials discovered in Menorca up to now, along with Es Càrritx, Es Mussol, and Es Pas. However, the chronology of Biniadrís is more extensive, covering more than seven centuries, allowing for a study of human practices over the “longue durée”. What makes Biniadrís unique is its large number of bioarchaeological remains, mainly human remains and other organic and inorganic material, in an extraordinary state of preservation. The main goal of this paper is to reconstruct the burial ritual using comprehensive bioarchaeological methods, including 14C radiocarbon dating, to understand the modality and temporality of use of the Biniadrís cave during the pre- and protohistory of the Balearic Islands. The palaeodemographic data derived from our ongoing excavation are described here in detail and point to interesting patterns, such as the equal representation of female and male individuals across all ages, including very young and older individuals. The fact that all individuals are equally represented and integrated into the community in the funerary settings provides insights into the group ideology, which are discussed further. These burial practices are interpreted as a strong expression of community identity at Biniadrís linked to its island setting, as seen from the preservation of the funerary memory over such a long period, which is unique for this cave. The multi-proxy approach employed here to study the bioarchaeological and organic remains contributes to a better understanding of the “longue durée” of the funerary ritual and the reconstruction of human behavior during the Late Bronze and Iron Ages of an island community in the western Mediterranean.